2011
DOI: 10.2217/pme.11.5
|View full text |Cite
|
Sign up to set email alerts
|

The Genome-Based Knowledge Management in Cycles Model: A Complex Adaptive Systems Framework for Implementation of Genomic Applications

Abstract: The main mission of the Genomic Applications in Practice and Prevention Network™ is to advance collaborative efforts involving partners from across the public health sector to realize the promise of genomics in healthcare and disease prevention. We introduce a new framework that supports the Genomic Applications in Practice and Prevention Network mission and leverages the characteristics of the complex adaptive systems approach. We call this framework the Genome-based Knowledge Management in Cycles model (G-KN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 73 publications
0
17
0
Order By: Relevance
“…[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Studies/reports were categorized according to the level of clinical health care addressed: the health care system (ie, strategic), an organization (ie, operational), or a team (ie, operational). Most commonly, studies targeted both organization and team levels (n = 11), [16][17][18][19][30][31][32][33][34][35][36] followed by the health care systems and organizations (n = 8). 15,[21][22][23][24][25]27,29 Gray literature studies most commonly addressed health care systems and organizations (n = 7), [21][22][23][24][25]27,29 whereas peer-reviewed studies most commonly addressed the organization and team levels (n = 11) (Supplemental File 5).…”
Section: Characteristics Of the Studies/reports Identifiedmentioning
confidence: 99%
See 3 more Smart Citations
“…[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Studies/reports were categorized according to the level of clinical health care addressed: the health care system (ie, strategic), an organization (ie, operational), or a team (ie, operational). Most commonly, studies targeted both organization and team levels (n = 11), [16][17][18][19][30][31][32][33][34][35][36] followed by the health care systems and organizations (n = 8). 15,[21][22][23][24][25]27,29 Gray literature studies most commonly addressed health care systems and organizations (n = 7), [21][22][23][24][25]27,29 whereas peer-reviewed studies most commonly addressed the organization and team levels (n = 11) (Supplemental File 5).…”
Section: Characteristics Of the Studies/reports Identifiedmentioning
confidence: 99%
“…15,[21][22][23][24][25]27,29 Gray literature studies most commonly addressed health care systems and organizations (n = 7), [21][22][23][24][25]27,29 whereas peer-reviewed studies most commonly addressed the organization and team levels (n = 11) (Supplemental File 5). [16][17][18][19]30,[32][33][34][35][36][37] Most studies/reports identified were driven by government bodies (n = 13), [21][22][23][25][26][27][28][29]31,[38][39][40][41] with 10 of these as government reports rather than research studies. [21][22][23][25][26][27][28][29]40,41 Another 13 were conducted by independent academics.…”
Section: Characteristics Of the Studies/reports Identifiedmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned earlier, HTA processes can be used, and additional frameworks for genome translation have already been proposed: for example, the 4 phases of translation presented by Khoury et al [12] and the ‘Genome-based Knowledge Management in Cycles' model by the GAPPNeT group [13]. In addition, criteria for responsible population screening have been proposed as refinements of the Wilson and Jungner criteria.…”
Section: What Is Public Health Genomics?mentioning
confidence: 99%